Physical Load Intensity in Standard and Latin American Sports Dancing Programmes for Juvenile Dancers - Aistė Barbora Ušpurienė; Algirdas Čepulėnas (Lithuanian Sports University, 2018)
Research background and hypothesis. Sports dances at the contest intensity demand great athletic fitness and functional capacity from dancers We still lack research about changes in the heart rate in the group of juvenile dancers' while dancing  Standard and Latin American dances. The present study aims at verifying the hypothesis that while juvenile dancers dancing contest programmes, the heart rate is changeable and can reach to 160-190 beats/min and above, sports dancers consume much energy. Research aim was to investigate changes in the heart rate and energy consumption in the group of juvenile dancers while dancing Standard and Latin American dances. Research methods. The research participants were 16 dancers (8 girls and 8 boys). The age of girls was 9.88 (0.83) years, and that of boys - 9.86 (1.07) years. We established changes in the heart rate dancing Standard and Latin American dances. During continuous dancing we registered the heart rate using "Polar S 610" Heart Rate Monitor (Finland) with computer data registering system. According to the indices received from the heart rate monitor we calculated the average, maximal and minimal heart rate values and energy consumption (kcal) during the period of sports dancing programme. Research results. The data of HR analysis showed that during a 10-min model practice session dancing Standard and Latin American dances, the heart rate which remains the longest is 160-190 beats/min. During Latin American dances, energy outlay for girls was greater than that for boys (p < 0.05), but lower compared to those when the girls danced the Standard programme. Discussion and conclusions. In contest programmes of sports dancing, physical loads are of changing intensities and thus they have a big impact on the cardiovascular system of young dancers. At the threshold of anaerobic intensity, some moments of the dance are performed at greater intensity then the anaerobic threshold, and even critical intensity limit is reached. Keywords Standard dances, Latin American dances, intensity of physical load, heart rate, energy consumption.